Android based letter recognition application with augmented reality implementation - Pramarta, Pandhu; Irfan, Irfan (Institute of Computer Science (IOCS), 2024)
Recognition of letters is an important basis in the process of learning to read in children. The use of Augmented Reality (AR) technology in education offers interactive methods that can increase interest and effectiveness of learning. This research aims to develop an Android-based application that uses AR to help children recognize letters. This application was developed using Unity 3D with the help of Vuforia SDK which allows effective implementation of AR. The methods used in this research include literature study, application design and development, as well as evaluation through technical testing and user testing. Testing is conducted to assess the functionality, user engagement, learning outcomes, and technical performance of the application. The results showed that the AR application was successful in improving letter recognition skills among children, with a high level of engagement and positive feedback from users. Although the application shows good performance on high-spec devices, technical challenges such as lag and frame rate drops on low-spec devices require further optimization. This research confirms the potential of AR as a valuable learning tool, especially in elementary education. The implications of this study suggest that further development and integration of AR technology in educational curricula can significantly improve the teaching and learning process, especially in facilitating distance learning and more immersive and interactive learning experiences. Further research is needed to explore possible applications of AR technology in broader educational contexts. Keywords: Augmented Reality, letter recognition, Unity 3D, Vuforia, children's education, learning applications.